Solving Quadratic Equations Using the Quadratic
Formula
When you solve an equation of the form ax^{2} + bx + c = 0, consider the following:
â€¢ If a = 0, then the equation can be written bx + c = 0.
This is a linear equation, not a quadratic equation.
So we cannot use the quadratic formula to solve it.
â€¢ If b = 0, then the equation can be written ax^{2} + c = 0.
We can solve using the quadratic formula with b = 0.
However, it takes fewer steps to solve this equation using
the Square Root Property.
â€¢ If c = 0, then the equation can be written ax^{2} + bx = 0.
We can solve using the quadratic formula with c = 0.
However, it takes fewer steps to solve this equation by factoring.
Note:
Hereâ€™s an example when a = 0:
3x + 5 = 0
a = 0, b = 3, c = 5
This is a linear equation.
Hereâ€™s an example when b = 0:
2x^{2} + 5 = 0
a = 2, b = 0, c = 5
Hereâ€™s an example when c = 0:
2x^{2} + 3x = 0
a = 2, b = 3, c = 5
